Genetic analysis of SARS-CoV-2 isolates collected from Bangladesh: Insights into the origin, mutational spectrum and possible pathomechanism. (February 2021) - Parvez, Md. Sorwer Alam; Rahman, Mohammad Mahfujur; Morshed, Md. Niaz; Rahman, Dolilur; Anwar, Saeed; Hosen, Mohammad Jakir
Graphical abstract: Highlights: Phylogenetic analysis revealed that SARS-CoV-2 isolates sequenced from Dhaka and Chittagong were the lineage of Europe and India, respectively. 42 mutations were identified and about half of them were synonymous. Identified missense mutations had less effect on viral pathogenesis. 3 large deletions were identified which cause loss of one or more proteins resulting in leading the virus less pathogenic. Effect of mutations on the interaction between spike proteins and human ACE2 was investigated by molecular docking approaches. A binding domain of spike protein was found to interact with human ACE2 which was conserved in all isolates. Abstract: As the coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), rages across the world, killing hundreds of thousands and infecting millions, researchers are racing against time to elucidate the viral genome. Some Bangladeshi institutes are also in this race, sequenced a few isolates of the virus collected from Bangladesh. Here, we present a genomic analysis of these isolates. The analysis revealed that SARS-CoV-2 isolates sequenced from Dhaka and Chittagong were the lineage of Europe and India, respectively. Our analysis identified a total of 42 mutations, including three large deletions, half of which were synonymous. Most of the missense mutations in Bangladeshi isolates found to have weak effects on the pathogenesis. Some mutations may lead the virus to be less pathogenic than the other countries. Molecular docking analysis to evaluate the effect of the mutations on the interaction between the viral spike proteins and the human ACE2 receptor, though no significant difference was observed. This study provides some preliminary insights into the origin of Bangladeshi SARS-CoV-2 isolates, mutation spectrum and its possible pathomechanism, which may give an essential clue for designing therapeutics and management of COVID-19 in Bangladesh.